Green organizational learning and sustainable work behavior in tourism and hotel enterprises: leveraging green intrinsic motivation and green training - Alhemimah, Arej; Baquero, Asier; Al-Romeedy, Bassam Samir; Khairy, Hazem Ahmed (Geojournal of Tourism and Geosites, 2024)
The global movement towards sustainability is gaining momentum. Therefore, the study investigates the impact of green organizational learning (GOL) on sustainable work behavior (SWB), examining the mediation roles of green intrinsic motivation (GIM) and green training (GT). The study used PLS-SEM technique and WarpPLS statistical software 7.0 to evaluate 475 replies from full-time employees at Saudi's five-star hotels and travel agencies. Findings revealed that GOL positively affects employees’ SWB, GIM, and GT. In addition, GIM and GT positively affect employees’ SWB and mediate the GOL→SWB relationship. The study provides new insights into how emerging concepts like GOL, GT, and GIM simultaneously predict the SWB within tourism and hospitality enterprises. The study also has the potential to contribute to Social Cognitive Theory. Furthermore, the study emphasizes the importance of green organizational learning in the tourism and hospitality sector for practical applications.
Keywords: green organizational learning; sustainable work behavior; green intrinsic motivation; green training; tourism and hotel enterprises